Strategic Planning of the Integrated Business and Information System – A Precondition for Successful Higher Education Management - Luić, Ljerka (Array, 2010)
This paper brings about the primary purpose of a research directed towards probing the insight into the presence of strategic planning at higher education institutions in the Republic of Croatia. The main conclusion of this paper sublimates the contribution to science and to the profession, and makes a new premise, that strategic planning of an integrated business-information system depends significantly upon long-term alignment of the management, which is in turn directly affected by common knowledge about the domain and funding. It therefore requires further in-depth research that needs to be conducted longitudinally, using an international sample, which would be as extensive as possible.